Cdk2 inhibition prolongs G1 phase progression in mouse embryonic stem cells - Koledova, Zuzana; Kafkova, Leona Raskova; Calabkova, Lenka; Krystof, Vladimir; Dolezel, Petr; Divoky, Vladimir (Stem cells and development, 2010)
Embryonic stem cells (ESCs) proliferate rapidly and have a unique cell-cycle structure with a very short G1 phase. Previous reports suggested that the rapid G1 phase progression of ESCs might be underpinned by high and precocious Cdk2 activity and that Cdk2 activity might be crucial for both cell-cycle regulation and cell-fate decisions in human ESCs. However, the actual role of Cdk2 in cell-cycle progression of mouse ESCs (mESCs) has not been elucidated. In this study, we investigated the effects of down-regulation of Cdk2 activity by olomoucine II in 2 mESC lines. Olomoucine II treatment significantly increased the G1 phase cell numbers, decreased the S phase cell numbers, and inhibited DNA replication in mESCs. In nocodazole-synchronized mESCs, we show that specific down-regulation of Cdk2 activity prolongs G1 phase progression. In addition, down-regulation of Cdk2 activity in mESCs established a somatic cell-like cell cycle and induced expression of differentiation markers. Our results suggest that high Cdk2 activity is essential for rapid G1 phase progression and establishment of ESC-specific cell-cycle structure in mESCs and support the hypothesis of a link between cell-cycle regulation and pluripotency maintenance in ESCs. This study reveals olomoucine II to be an effective tool for manipulation of the cell cycle and pluripotency in ESCs and very likely also for the manipulation of other stem cell types, including cancer stem cells.
Keywords: Mice, Inbred Strains; cyklin-dependentní kinasa 9; Animals; buněčné linie; Inhibitory Concentration 50; Blotting, Western; průtoková cytometrie; inbrední kmeny myší; Cell Cycle; puriny; Time Factors; časové faktory; lidé; Mice; replikace DNA; Flow Cytometry; inhibiční koncentrace 50; Cyclin-Dependent Kinase 9; polymerázová řetězová reakce s reverzní transkripcí; myši; Cell Line; buněčný cyklus; western blotting; G1 fáze; cyklin-dependentní kinasa 2; Reverse Transcriptase Polymerase Chain Reaction; embryonální kmenové buňky; proteinkinasa CDC2; Purines; G1 Phase; CDC2 Protein Kinase; Cell Survival; zvířata; Cyclin-Dependent Kinase 2; viabilita buněk; HT29 Cells; DNA Replication; Mice, Inbred C57BL; buňky HT-29; Embryonic Stem Cells; myši inbrední C57BL; Humans